Desenvolvimento de método por cromatografia líquida bidimensional abrange para documentação química de extratos vegetais e estudos metabolômicos - Leme, Gabriel Mazzi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Despite recent advances in monodimensional liquid chromatography, the complexity of some samples requires the use of separation techniques that can provide greater resolving power and peak capacity. As a consequence, the development of comprehensive two-dimensional chromatographic techniques (LC×LC, GC×GC, LC×LC) has received increasing attention in recent years. The main advantage of these techniques compared to traditional techniques is the largest peak capacity and possibility to employ different separation mechanisms in each dimension. The biggest challenge related to method optimization of this kind of techniques is related to the selection of complex experimental parameters, often based on the analyst's experience rather than theoretically based strategies. The first and most important step in the method optimization process in LC×LC is the selection of the chromatography pair (stationary phase and mobile phase, 1D and 2D). When the sample is precisely known, some features may serve as qualitative guidance in the selection of these parameters; in other cases, representative standards can be used to evaluate the correlation between 1D and 2D systems, however, when little or no information is available, this remains a difficult task. This work presents a new strategy for the selection of the chromatographic pair using real and extremely complex samples and fractional coverage surface calculations, besides the method optimization in comprehensive two-dimensional liquid chromatography based on statistical designs. The sample selected for the method development was a mixture of plant extracts previously studied by the research group and containing a wide diversity of metabolites with distinct structural characteristics and therefore different challenges to be overcome in the chromatographic separation. Employing such strategy and comprehensive elution conditions, it was possible to select the...

Apesar dos recentes avanços em cromatografia líquida monodimensional, a complexidade de algumas amostras exige o emprego de técnicas de separação capazes de oferecer maior poder de resolução e capacidade de picos. Como consequência, o desenvolvimento de técnicas cromatográficas bidimensionais abrangentes (LC×LC, GC×GC, LC×GC) tem recebido atenção crescente nos últimos anos. A principal vantagem dessas técnicas comparadas às técnicas tradicionais é a maior capacidade de picos e possiblidade de se empregar diferentes mecanismos de separação em cada dimensão. O maior desafio relacionado à otimização de métodos desta natureza está relacionado à seleção de complexos parâmetros experimentais, frequentemente baseada na experiência do analista ao invés de rigorosamente estruturada em estratégias teoricamente embasadas. A primeira e mais importante etapa no processo de otimização de métodos LC×LC é a seleção do par cromatográfico (fase estacionária e fase móvel, 1D e 2D). Quando a amostra é precisamente conhecida, algumas características podem servir como um guia qualitativo na seleção destes parâmetros; em outros casos, padrões representativos podem ser empregados para avaliar a correlação entre os sistemas 1D e 2D, porém, quando pouca ou nenhuma informação é disponível, esta continua sendo uma tarefa difícil. Este trabalho apresenta uma nova estratégia de seleção do par cromatográfico empregando amostras reais de extrema complexidade e cálculos de recobrimento da superfície de separação, além da otimização de métodos em cromatografia líquida bidimensional abrangente baseada em planejamentos estatísticos. A amostra selecionada para o desenvolvimento do método foi uma mistura de extratos vegetais previamente estudados pelo grupo de pesquisa, contendo uma vasta diversidade de metabólitos com diferentes características estruturais e...
Keywords: Cromatografia liquida; Metabolômica; Produtos naturais; Datiloscopia; Liquid chromatography